Low-stress mechanical properties of dual bio-pre-mordanted catechu-dyed cotton fabrics subsequently bio-finished with Eucalyptus leaf extract, nano-chitosan and nano-ZnO: NIL (Indian Journal of Fibre & Textile Research (IJFTR), 2026)
AbstractThe earlier part of the study, reported elsewhere, evaluated the results of bio-dyeing of cotton fabrics with catechu natural bio-dye using potash alum (K-alum) + Gallnut (GN) dual pre-bio-mordanting to achieve maximum colour strength with overall good colour fastnesses to washing, rubbing and UV-light exposure. The present part of the study evaluates the efficacy of three different bio-finishing (after dyeing) methods using eucalyptus leaf extract, nano-chitosan, and nano-ZnO to improve their antimicrobial and UV resistance properties to the maximum level possible. Skin sensory tactical comfort properties in terms of responses to tensile loading/ stretching, shearing, bending, compression, surface friction (roughness) under low-stress conditions as primary hand values and resultant total hand values of the said dual bio-mordanted and catechu dyed and subsequently bio-finished with above said three different bio-finishes, were evaluated with Kawabata Evaluation System (KES). The said KES analysis revealed an overall increase in thickness (approx. 4- 67 %), weight per sq. centimeter of the fabric (approx. 16- 27 %), and coefficient of friction (approx. 32- 62 %) after application of the said bio-finishes. Still, as per resultant total hand value analysis, all these bio-finished fabrics are found not suitable for men's shirting in summer, but are found suitable for women's dress materials for the winter/autumn season. Simultaneously, Eucalyptus leaf extract bio-finished catechu dyed cotton fabrics had shown excellent UV protection factor of 45-50 with 98-99 % bacterial reduction in specific conditions of treatment, while nano-ZnO bio-finished catechu dyed cotton fabric had also exhibited maximum reduction in bacterial growth (98- 99 %) and nano chitosan did not show that level of very good results for antimicrobial and UV-protective criteria. Thus, both Eucalyptus leaf-extracted and nano-ZnO bio-finished fabrics have shown their potential for use as medical textile applications due to improved functional properties. Keywords: Bio-finish, Bio-medical textiles, Cotton, Catechu, Eucalyptus leaves,  Kawabata Evaluation System, Mordanting, Nano-Chitosan, Nano-ZnO, Total Hand Value.